Self-affirmation improves self-control over snacking among participants low in eating self-efficacy. (1st April 2018) - Churchill, Susan; Jessop, Donna C.; Green, Ricky; Harris, Peter R.
Abstract: Objective: Individuals low in eating self-efficacy are at particular risk of engaging in unhealthy eating behaviours, including the consumption of high calorie snacks. The elevated levels of snacking displayed by these individuals can largely be attributed to their experiencing low self-control over the avoidance of such foods (Hankonen, Kinnunen, Absetz, & Jallinoja, 2014). Interventions are thus required to boost self-control over snacking among those low in eating self-efficacy. Self-affirmation has been shown to boost self-control among individuals with depleted resources in other domains (Schmeichel & Vohs, 2009). The purpose of the current study was to test the hypothesis that a self-affirmation manipulation would similarly increase self-control over snacking for individuals low in eating self-efficacy. Methods: At baseline, participants ( N = 70) completed measures of dietary restraint and eating self-efficacy. In the main study, participants completed either a self-affirmation or a control task immediately before undertaking a joystick category judgment task that assessed self-control over snacking. Results: Hierarchical multiple regression analysis revealed the predicted significant interaction between eating self-efficacy and self-affirmation, demonstrating that self-affirmation moderated the association between eating self-efficacy and self-control over snacking. Johnson-Neyman regions of significance confirmed that for participants low in eating self-efficacy the self-affirmation manipulation resulted in higher levels of self-control. Unexpectedly, however, for participants high in eating self-efficacy the self-affirmation manipulation was found to be associated with lower levels of self-control. Conclusions: Findings supported the hypothesis that a self-affirmation manipulation would boost self-control over snacking among individuals low in eating self-efficacy. Self-affirmation may thus provide a useful technique for strengthening self-control in relation to the avoidance of unhealthy foods among individuals who find it difficult to manage challenging dietary situations.